Developing Local Culture-Based Listening Materials through Digital Storytelling - Sinaga, Juwita Boneka; Saputro, Isnaini Eddy; Yulianingsih, Lilik; Dewi, Desi Surlitasari; Subrata, Doni; Ardhi, Mega Aulia (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to develop and evaluate digital storytelling-based listening materials that integrate the local culture of Riau Islands to enhance students' listening comprehension. The research employed a Design-Based Research (DBR) approach involving iterative cycles of design, development, implementation, and evaluation. The participants consisted of 35 university students, three lecturers, and three experts in material, language, and media validation. Data were collected through questionnaires, expert validation forms, and pre-test–post-test assessments. The design phase resulted in audiovisual storytelling materials featuring local cultural narratives and interactive comprehension activities. Expert validation indicated that the materials were highly feasible, with mean scores above 85% across material, language, and media aspects. The implementation results revealed a significant improvement in students' listening comprehension, as shown by an increase in the mean score from 61.31 (pre-test) to 80.89 (post-test) with a mean gain of 19.57 points (p .001). The findings suggest that digital storytelling enriched with local culture can serve as an effective and engaging alternative medium for listening instruction. This study contributes to the integration of culturally grounded digital pedagogy in language learning and supports the contextualization of English instruction in multicultural settings.